A gênese da subjetividade ética desde o paradigma da sensibilidade: a significação ética como orientação responsiva e tensão individuante em lévinas - Cerezer, Cristiano (2016)
The aim of our work is to approach the theme of the genesis of ethical subjectivity in E. Lévinas, in an attempt to understand - from the author - how the processes of subjectivation of the self imply those of moralization and how the sensitive conditions of the subject in formation serve of basic field for the establishment of the first meaningful relationships from which the "order of meaning" is introduced into the "order of being", tensioning with it. According to the Lithuanian thinker, this "institution of signification" is ethical and installs itself from the sensibilization/incarnation of nascent subjectivity. Thus, it seems to us that sensitivity/sensibility has, in Lévinas, a dual function: 1) Conditioning; 2) Paradigmatic. We will try to analyze in what sense the "conditions of genesis" are sensitive/sensibles and to expose the paradigm of the sensibility within which the Levinasian critique of ontology and the rescue of alterity and heteronomy work as what conditions the ethical signification in a more original way. To do so, we will cover aspects such as: i. The tension between singularization and totalization in signification linked to subjective individuation; ii. The role of corporeality in ethical theory and the passage from the phenomenology of moral subjectivity to a possible phenomenological ethics; iii. The possible repercussions of the "Levinasian paradigm" - based on ethical sensitivity and heteronomy - on the definition of an "ethic of otherness". Thus, ethical significance will be composed of two articulated elements: a) Individuating tension; B) Responsive Guidance/Orientation. We will map the contours and essential elements of this articulated meaning from the paradigmatic condition of the sensibility as the soil from which an ethic of alterity emerges.